Analysis of Solar Radiation Measurements in Kathmandu, Nepal - Maharjan, Arbin; Maharjan, Kabina (Journal of Engineering Issues and Solutions, 2026)
Solar radiation measurement is essential to predict a better output from the solar power installations. This paper presents an analysis of solar radiation measurements obtained for a period of six months (January to June, 2019) from a solar station installed in Kathmandu, Nepal (27.6815° N 85.3186° E). Direct Normal Irradiance (DNI) is measured by pyrheliometer whereas, Diffuse and Global Horizontal Irradiances (DHI and GHI) are measured by pyranometers. The sensors are thermopile based and are mounted on a 2D-solar tracker at a height of 2m. The data are recorded at a minute interval in a data logger and are analyzed to obtain daily and monthly average values. The maximum daily average is found on March 12 (GHI=471.92 W/m2, DNI=570.6 W/m2) and June 30 (DHI=247.15 W/m2) whereas, the minimum daily average was all found on April 6 (GHI=79.73 W/m2, DNI=3.81 W/m2 and DHI=83. 27 W/m2). The six months average of GHI, DNI and DHI are found to be 322.49, 308.735 and 156.177 W/m2 respectively. The maximum monthly average is found on March (GHI=374.56 W/m2, DNI=387.75 W/m2) and June (DHI= 188.89 W/m2) whereas, minimum monthly average is on Jan (GHI=256.4 W/m2, DHI=124.19 W/m2) and June (DNI=250.25 W/m2). The monthly average of DNI is found to be greater than GHI for the winter months (Jan-March) whereas, it’s opposite for the summer months (Apr-Jun). A min by min plot for a particular day on a winter month and hourly average values of GHI and DNI plots for a 21st day of each month is also presented to support the finding.